Wind hazard mapping in Peninsular Malaysia using geographical information system - Muhammad Zulfikri, Ibrahim (2016)
Recently the increasing of wind related disaster numbers are frequently being reported in Malaysia. Wind hazard map distributions are widely used in wind engineering filed in estimating the potential of the risk specific area. However, most of the wind hazard map only considering extreme wind without incorporating other factors such as topographic and land use land cover. Therefore, this study presented the result of wind hazard map that integrated with other relevant factors. Three factors including extreme wind speed, hill slope and land cover type were used in this study. GIS based model used for generating the wind hazard map. The wind related damage inventory which has a total, of 93 locations was created based on numerous resources such as a national newspaper archive. From the result in clearly shown that the skewness analysis given negative result which is means the tendency of the damage location are located at the high wind prone area. The validation of the result also shows that integrated wind hazard with others relevant factors give improved results compare to the conventional wind speed. For that reason this present wind risk map produce in this study would be useful for a hazard mitigation purpose and regional planning.